Conserved loci of leaf and stem rust fungi of wheat share synteny interrupted by lineage-specific influx of repeat elements - Fellers, John P.; Soltani, Bahram M.; Bruce, Myron; Linning, Rob; Cuomo, Christina A.; Szabo, Les J.; Bakkeren, Guus (My University, 2013)
Background: Wheat leaf rust (Puccinia triticina Eriks; Pt) and stem rust fungi (P. graminis f.sp. tritici; Pgt) are significant economic pathogens having similar host ranges and life cycles, but different alternate hosts. The Pt genome, currently estimated at 135 Mb, is significantly larger than Pgt, at 88 Mb, but the reason for the expansion is unknown. Three genomic loci of Pt conserved proteins were characterized to gain insight into gene content, genome complexity and expansion. Results: A bacterial artificial chromosome (BAC) library was made from P. triticina race 1, BBBD and probed with Pt homologs of genes encoding two predicted Pgt secreted effectors and a DNA marker mapping to a region of avirulence. Three BACs, 103 Kb, 112 Kb, and 166 Kb, were sequenced, assembled, and open reading frames were identified. Orthologous genes were identified in Pgt and local conservation of gene order (microsynteny) was observed. Pairwise protein identities ranged from 26 to 99%. One Pt BAC, containing a RAD18 ortholog, shares syntenic regions with two Pgt scaffolds, which could represent both haplotypes of Pgt. Gene sequence is diverged between the species as well as within the two haplotypes. In all three BAC clones, gene order is locally conserved, however, gene shuffling has occurred relative to Pgt. These regions are further diverged by differing insertion loci of LTR-retrotransposon, Gypsy, Copia, Mutator, and Harbinger mobile elements. Uncharacterized Pt open reading frames were also found; these proteins are high in lysine and similar to multiple proteins in Pgt. Conclusions: The three Pt loci are conserved in gene order, with a range of gene sequence divergence. Conservation of predicted haustoria expressed secreted protein genes between Pt and Pgt is extended to the more distant poplar rust, Melampsora larici-populina. The loci also reveal that genome expansion in Pt is in part due to higher occurrence of repeat-elements in this species.
Citation: Fellers, J., . . . & Bakkeren, G. (2013). Conserved loci of leaf and stem rust fungi of wheat share synteny interrupted by lineage-specific influx of repeat elements. BMC Genomics, 40, 60. https://doi.org/10.1186/1471-2164-14-60
Keywords: Wheat leaf rust; BAC construction; Synteny